Oral health care and service utilisation in individuals with Rett syndrome: an international cross‐sectional study. Issue 6 (25th March 2021) - Lai, Y. Y. L.; Downs, J.; Zafar, S.; Wong, K.; Walsh, L.; Leonard, H.
Abstract: Background: There is a dearth of literature available on the comparative oral health status of those with Rett syndrome (RTT) despite diurnal bruxism being a supportive diagnostic criterion for the disorder. This study was designed to investigate the dental experiences of individuals with RTT in terms of perceived at‐home and professional dental care. Methods: Using data in the InterRett database, provided by English‐speaking families of individuals with a confirmed MECP2 genetic mutation, the study investigated relationships between dental problems, oral care, child factors including bruxism and use of gastrostomy, and socioeconomic indicators. The study also explored relationships between dental presentations and socioeconomic, child, and family‐related factors. Results: Individuals with RTT exhibiting bruxism were more likely to access dental treatment. Those who had full oral feeding had a higher incidence rate of dental treatment than those with full tube feeding. A conservative (under) estimation of the overall dental caries progression rate revealed that this may be similar to that of the normal population. Conclusions: Drivers for dental treatment in RTT include bruxism as well as dental caries. Those who have full oral feeding experience more dental treatment than those with full tube feeding. A higher maternal education level may confer a protective effect for oral health outcomes in those with RTT. Nevertheless, families generally tended to value the importance of oral health despite reported difficulties in day‐to‐day mouth care.